Fødevarer og sundhed i senmodernismen: En indsigt i hyggefænomenet og de relaterede fødevarepraksisser - Heidi Boye (Copenhagen Business School (CBS), 2010)
– A lot of attention has been given to health-related issues worldwide, especially since the World Health Organisation declared obesity epidemic in many countries. Overweight and obesity impose a serious threat to economic welfare and the health and quality of life of the individual consumer (Indenrigs- og Sundhedsministeriet, 2007). Paradoxically in continuation of the increased overweight, obesity and nutrition-related diseases research stresses there is an escalating concern about health issues such as eating and living healthy (ATV, 2007; Nordic Plan of Action, 2006). However consumers find many different obstacles to integrating healthy food products in their daily lives, including the compelling need for hedonic food consumption which often involves less healthy or unhealthy food (Luomala et al., 2004, 2006). Hedonic food consumption is often associated with social gatherings and ,,hygge42‟, where everyday ,,health-rules‟ are replaced with unrestricted ,,pleasure-rules‟......
hdl:10398/8050
Keywords: 650